Heracleum persicum L. extract protects gentamicin-induced testicular toxicity - Elnaz Khordad; Mohsen Akbaribazm; Seyed Moein Hosseini (Avicenna Journal of Phytomedicine)
Objective: The objective of this study was to assess the protective effects of Heracleum persicum L. leaves extract (HPE) against oxidative damage induced by gentamicin (GM) in the testes of rats through biochemical, histopathological, and immunohistochemical approaches. Materials and Methods: Thirty-six male Wistar rats were divided into six groups (n=6/group) for 50 days. On day 51, the study assessed serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone (TT), as well as antioxidant enzyme activity, nitric oxide levels, and various parameters related to testicular tissue (including the ferric reducing ability of plasma (FRAP), thiol, and thiobarbituric acid reactive substances (TBARS) levels). The stereological indices of seminiferous tubules were measured using serial sections of testicular tissue stained with hematoxylin and eosin, while the apoptosis rate of testicular parenchymal cells (p53, Caspase-3, and Bcl-2 positive cells) was also determined.Results: In the groups treated with HPE, particularly at 750 mg/kg, there was a significant increase (p<0.05) in LH, FSH, and TT hormone levels,  an enhanced serum antioxidant enzyme activity and significantly reduced (p<0.05) nitric oxide levels. HPE inhibited the apoptotic pathway involving Bax/p53/Caspase-3 (significantly decreased (p<0.05) all three genes), thereby preserving the structure and function of the testicular tissue. Consequently, the number of p53 and Caspase-3 positive testicular cells decreased significantly (p<0.05), while the number of Bcl-2 positive cells increased. Conclusion: HPE demonstrated potential in protecting the function and structure of testis against toxic and oxidative damages.